Examining Inhibitory Affective Processing Within the Rostral Anterior Cingulate Cortex Among Abstinent Cannabis-Using Adolescents and Young Adults - Sullivan, Ryan M.; Maple, Kristin E.; Wallace, Alexander L.; Thomas, Alicia M.; Lisdahl, Krista M. (Frontiers in Psychiatry, 2022)
Cannabis use has been associated with deficits in self-regulation, including inhibitory control. Cannabis users have previously exhibited both structural and functional deficits in the rostral anterior cingulate cortex (rACC), a region involved in self-regulation of emotional response and inhibitory control. The present study aimed to examine whether abstinent cannabis users demonstrated abnormal functional activation and connectivity of the bilateral rACC during an emotional inhibitory processing task, and whether gender moderated these relationships. Cannabis-using (N=34) and non-using (N=32) participants ages 16-25 underwent at least two-weeks of monitored substance use abstinence (excluding tobacco) and fMRI scanning while completing a Go/No-go task using fearful and calm emotional faces as non-targets. Multiple linear regression and ANCOVA were used to determine if cannabis group status was related to rACC activation and context-dependent functional connectivity, and whether gender moderated these relationships. Results showed decreased bilateral rACC activation in cannabis users during fearful response inhibition, although groups did not show any context-dependent connectivity differences between the left or right rACC during calm or fearful inhibition. Gender findings revealed that cannabis-using females compared to males did show aberrant connectivity between the right rACC and right cerebellum. These results are consistent with literature demonstrating aberrant structural and functional rACC findings and suggest that chronic cannabis use may disrupt typical rACC development—even after abstinence—potentially conferring risk for later development of mood disorders. Marginal gender-specific connectivity findings bolster continued findings regarding female vulnerability to effects of cannabis on cognition and affect. Findings should be assessed in longitudinal studies to determine causality and timing effects.